Mr. M and Mr. D´s refuge - Tania Ugena Candel; Berta de la Dehesa Amo (Arteterapia)
The cases presented in this article are two participants in project ACTION * CREATION. This project is part of ARIADNE, a European research that aims to systemize art methods to facilitate the adjustment of immigrants and to help reduce their stress and contribute to the development of their feelings (i.e.: homesickness, death etc.) thus validating the usefulness of art and creative processes as tools to alleviate the negative effects of the migration process. This project was developed in a political refugee center in Madrid from October 2011 to February 2012, where the asylum seekers reside waiting their resolution of refuge. The workshop involved asylum seekers and other residents whose status was irregular. The group was composed of migrants of various nationalities and ages (children, pre-teens and adults).